Use of First Language in the Classroom: Non-native EFL Teachers’ Beliefs in Teaching English to Adult Learners in Bilingual Context - Ahmad, Iftikhar; Noor Raha, Mohd Radzuan; Hussain, Muhammad Sabboor (AWEJ.org, 2018)
This study aims to investigate the perspectives of non-native English as a Foreign Language (EFL) teachers across mother tongue and gender, and their male and female adult students, regarding the use of Arabic in the EFL classrooms at the university level in Saudi Arabia. The study specifically seeks to investigate the perspectives of non-native Arab and non-Arab EFL teachers as they, working in the native Arab setting, often resort to Arabic (Al-Nofaie, 2010; Machaal, 2012). However, there are glaring research gaps about non-native EFL teachers’ and adult learners’ beliefs on the use of first language (L1) in the classroom. For this purpose, the study used quantitative research design, and administered two questionnaires, one for the teachers and the other for the students. Students’ questionnaire complemented that of the teachers. Forty teachers and sixty students were selected based on stratified random sampling. The findings of the study revealed that all camps of teachers, Arab, non-Arab, male, female, and students were in favour of judicious bilingual approach. The study finds statistically significant difference between the beliefs of Arab and non-Arab EFL teachers about the use of L1. The findings suggest that Arab EFL teachers’ use of Arabic is extensive, while non-Arab EFL teachers’ use of Arabic is well-timed. The study suggested practical implications for the improvement of English Language Teaching (ELT) in Saudi Arabia by recommending planned, occasional and judicious use of L1 while teaching EFL adult learners.